MANAJEMEN USAHA PERIKANAN DENGAN ALAT TANGKAP BAGAN APUNG DI DESA ARAKAN KECAMATAN TATAPAAN KABUPATEN MINAHASA SELATAN PROPINSI SULAWESI UTARA - Kabanulu, Ludia; Rantung, Steelma V.; Suhaeni, Siti (Universitas Sam Ratulangi, 2018)
A decent standard of living can only be enjoyed if it has high income and to obtain high income productivity is also high. High productivity can only be achieved through business improvement. Improvements can be made through various approaches, but the most widely used is management or management. Management approach is widely used because it can run and control the business.The village of Arakan is one of the coastal villages whose average population works as fisherman and most are traditional fishermen. Traditional catching tools commonly used such as arrows (jubi), fishing rods, nets and charts. The chart capture tool used in Arakan Village is a floating chart. Based on the information obtained on the state of the fishery business with the existing fishing gear in Arakan Village shows that, there were 12 floating bussiness business that was run, but now only 6 units are able to survive and develop. Such information raises the intention to conduct research to see, learn and know the existing management of the business.The purpose of this research is to study the management of fishery business with the catching tool chart in Arakan Village, viewed from: a. aspects of production, b. financial aspects, c. aspects of marketing.The basic method used in this research is case study method. Data collection technique is done by census. The data collected in this research consist of primary data and secondary data. Data analysis used is descriptive qualitative and quantitative analysis.The result of the research shows that fishery business management with floating fishing gear in Arakan Village is seen from 3 aspect, that is production, finance and marketing run well, seen with the implementation of management functions such as planning, organizing, movement, and supervision. Viewed from the financial aspect of the business is also very profitable. This is seen from the investment payback period of only 3.1 months. Implementation of all management functions on floating business in Arakan Village is controlled by the owner.Keywords: management, fishery business, floating chart, business owner